2004
DOI: 10.1002/bit.20263
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of shear stress and streptavidin‐biotin on the expression of endothelial vasodilator and cytoskeleton genes

Abstract: Dual ligand treatment of streptavidin(SA)-biotin and fibronectin (Fn) enhances the adhesion of endothelial cells (EC) onto synthetic surfaces and promotes the quiescent phenotype of adherent EC. The current study investigates the effect of the dual ligand on the expression of endothelial genes in static culture and under shear stress (4 h at 10 dynes/cm2). Expression of 23 genes in the classes of signaling, cytoskeleton/ECM, vasoregulation, and shear-responsive were examined. Eight genes (argininosuccinate syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The genes chosen had all been shown to be sensitive to shear stress in vitro at the mRNA and/or protein level in a variety of endothelial cell types. 2,8,15,16,18,19,22,23,26 Consistent with the global tendencies revealed by microarray analysis, qPCR also showed that positive and negative deviations from moderate levels of shear stress were associated with similar gene expression responses. Among the seven genes studied by qPCR, the expression levels of four of them (b-catenin, c-jun, VCAM-1, and MCP-1) were altered in both the low shear and high shear environments relative to the medium shear environment (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…The genes chosen had all been shown to be sensitive to shear stress in vitro at the mRNA and/or protein level in a variety of endothelial cell types. 2,8,15,16,18,19,22,23,26 Consistent with the global tendencies revealed by microarray analysis, qPCR also showed that positive and negative deviations from moderate levels of shear stress were associated with similar gene expression responses. Among the seven genes studied by qPCR, the expression levels of four of them (b-catenin, c-jun, VCAM-1, and MCP-1) were altered in both the low shear and high shear environments relative to the medium shear environment (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Thus the capacity of endothelial cells to sustain NO production is severely limited not only by the downregulation of eNOS (2,4,36) but also by the availability of arginine provided by AS via the citrulline-NO cycle. Coordinate upregulation of AS and eNOS expression has been identified previously in a number of systems (10,30). For example, AS and eNOS are coordinately induced in the aorta of diabetic rats after streptozotocin treatment (30).…”
Section: Discussionmentioning
confidence: 95%
“…NO is utilized in signaling, whereas citrulline is recycled back to arginine by two enzymes, argininosuccinate synthase (AS) and argininosuccinate lyase, to complete the cycle. AS catalyzes the rate-limiting step in the arginine regeneration side of the citrulline-NO cycle (42) and appears to be coordinately regulated with eNOS activity (10,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biotin and avidin mediated binding has previously been shown to enhance endothelial cell (EC) attachment, spreading, and a quiescent phenotype on synthetic surfaces. [23][24][25][26] These attributes may assist in targeting cells to vascular surfaces exploiting the strong interaction between biotin and avidin. Modification of vascular surfaces with protein-reactive PEG-biotin might thus provide a target for the site-specific delivery of microspheres and cells under physiologic flow conditions following intravascular procedures such as angioplasty or end-arterectomy.…”
Section: Introductionmentioning
confidence: 99%